Листи К.К. Косцюшка-Валюжинича до К. В. Болсуновського (за матеріалами наукового архіву Національного музею історії України) - Попельницька, О.О. (Археологія, 2023)
У статті розглянуто два листи К. К. Косцюшка-Валюжинича до К. В. Болсуновського, що висвітлюють окремі аспекти археологічного вивчення Херсонеса в 1902 р. In the archives of the National Museum of the History of Ukraine in the fund of K. V. Bolsunovskyi there are two letters from
K. K. Kościuszko-Waluszyński, dated by 1902. The author of these letters, Karol Kościuszko-Waluszyński, from 1888 had
been heading the Museum in Chersonesus and conducted excavations of this ancient city. The recipient of these letters, Karl
Bolsunovskyi, was a well-known expert numismatist and connoisseur of ancient coins.
K. K. Kościuszko-Waluszyński and K. V. Bolsunovskyi not only corresponded, but were also personally acquainted. This
is evidenced by the lines of the letter of K. K. Kościuszko-Waluszyński dated by September 12, 1902. K. V. Bolsunovskyi could
have met K. K. Kościuszko-Waluszyński during one of his visits to the museum in Chersonesus.
The novelty and relevance of the research lies in the study of professional and personal contacts of the representatives of
Kyiv scientific elite K. V. Bolsunovskyi and B. I. Khanenko with the Crimean researcher K. K. Kościuszko-Waluszyński on the
field of archaeology and numismatics.
These documents contain information about individual aspects of the activities of the Chersonesus museum, as well as
about personal contacts of Kyiv and Crimean scholars that had taken place at the beginning of the 20th century. The letters
contain references to the organization of the museum's territory, the creation of a project for a new museum building and the
organization of excavations at the end of 1902 — the beginning of 1903. For instance, in a letter to K. V. Bolsunovskyi, dated by
September 12, 1902, K. K. Kościuszko-Waluszyński mentioned plans to build a new museum building, choosing a construction
site, carrying out measurements on the site, drawing up plans for the future museum and an estimate of its construction.
These letters also characterise K. K. Kościuszko-Waluszyński as an energetic, inquisitive, benevolent and hospitable
person, a conscientious researcher and museum officer, who sought to establish contacts with Kyiv scholars in order to identify
analogies to the finds from Chersonesus, exchange professional literature and attribution of the discovered finds.